A combined technique for acromioclavicular reconstruction after acute dislocation - technical description and functional outcomes - Diogo Lino Moura; Augusto Reis e Reis; João Ferreira; Manuel Capelão; José Braz Cardoso (Revista Brasileira de Ortopedia)
ABSTRACT Objective: This study aims to describe the surgical approach to such injuries and to present the clinical and functional outcomes obtained in a cohort of patients. Methods: This is an observational retrospective study that included 153 patients with acute acromioclavicular joint dislocation, operated between 1999 and 2015. Clinical evaluation included the following outcomes: Constant functional scale, development of complications, time to return to previous work/sport activities, and satisfaction index. The contra-lateral (uninjured) shoulder was used as control in subjective outcomes. Radiological evaluation was performed in order to monitor signs of loss of reduction, degenerative joint changes, and coracoclavicular calcifications. Results: The mean age was 29.20 ± 9.53 (16-71), with a large male predominance (91.5%). Follow-up lasted 55.41 ± 24.87 (12-108) months. The mean Constant score attained was 96.45 ± 4.00 (84-100) on operated shoulders and 98.28 ± 1.81 (93-100) on contralateral ones. Almost all patients (98.69%) were satisfied with the surgical results. Worse outcomes were observed in acromioclavicular joint dislocations of increasing grade (from type III to V, but worse for type IV), both concerning the Constant score and return to work or sport. The overall incidence of complications was considered low, with the most prevalent being Kirschner wire failure and isolated coracoclavicular ligament calcifications. Conclusion: The surgical technique described is an excellent option in the treatment of acute acromioclavicular joint dislocations of Rockwood grades III to V. This is corroborated by the excellent clinical and functional outcomes and the low rate of complications.